Pembelajaran Biologi Berbasis Praktikum dan Kemampuan Berpikir Kritis Siswa : Sebuah Kajian Korelasi: Praktikum Dalam Pembelajaran Dapat Meningkatkan Kemampuan Berpikir Kritis Siswa - Nadia Nur Khamilah Al-hafidz; Alay Fia; Adinda Zhafarah; Ade Suryanda (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Education is very important for the development of a country. Countries with high educational standards are considered developed. Skills in critical analysis are vital to advancing the nation and oneself in the 21st century and also to provide experience as an important asset to compete in the future. The aim of this research is to determine the relationship between learning using practical methods and its impact on students' critical analysis skills. In this research, a descriptive analysis method was used to describe the problem of a correlation study in practicum-based learning with students' critical analysis skills. The data collection technique used was the literature study method. The literature taken is based on previous research related to the topic. Research shows that practicum-based learning is considered useful in honing critical analysis skills, stimulating initiative, learning motivation, and establishing collaboration. The results obtained are that practicum-based learning is able to improve students' critical analysis skills by increasing student activity during practicum learning. These active students encourage students to do their practicum well and can get answers to unsolved problems.